Discrete Mathematics for Computer Science : An Example-Based Introduction - Fortney, Jon Pierre (CRC Press, 2021)
Discrete Mathematics for Computer Science: An Example-Based Introduction is intended for a first or second-year discrete mathematics course for computer science majors. It covers many important mathematical topics essential for future computer science majors, such as algorithms, number representations, logic, set theory, Boolean algebra, functions, combinatorics, algorithmic complexity, graphs, and trees. Features designed to be especially useful for courses at the community college level Ideal as a first or second-year textbook for computer science majors, or as a general introduction to discrete mathematics Written to be accessible to those with a limited mathematics background and to aid with the transition to abstract thinking Filled with over 200 worked examples, boxed for easy reference, and over 200 practice problems with answers. Contains approximately 40 simple algorithms to aid students in becoming proficient with algorithm control structures and pseudocode. An appendix on basic circuit design provides a real-world motivational example for computer science majors by drawing on multiple topics covered in the book to design a circuit that adds two eight-digit binary numbers.